PERUBAHAN PERANAN WANITA SUNDA: STUDI KASUS DI KOTA BANDUNG - Siti Komariah (TEMALI : Jurnal Pembangunan Sosial, 2019)
This writing explores the sociology of family, especially related to the roles of women in Sundanese societal family, by taking the case of the City of Bandung. By qualitative and survey approaches, the writer apprehends the matters by tracking to women’s job; the age of marriage and the right to choose the spouse; the view of women towards the roles of wife, husband, mother; and their views on jobs and domestic issues. The writer finds out that Sundanese women have got a new condition, like those of breadwinning roles, etc.